The experience of caregiver: old age person in family - Užaitė, Vytautė; Naujanienė, Rasa (Socialinė teorija, empirija, politika ir praktika, 2006)
The goal of the paper is to review the studies, where the peculiarities of home care of old age people are analysed, and present the research, where the experiences of relative carers of old age incurable people. The authors employed the qualitative research strategy. There were four informants: three women and one man. The data analysis suggests the relatives start to care for incurable old age person, when there are not reversible health changes and they are diagnosed. The meaning of care process is the same as the ordinary help between the family members.
Keywords: Old age person; Home care; Family members